2015
DOI: 10.1039/c4ra15670f
|View full text |Cite
|
Sign up to set email alerts
|

LED lighting as a simple, inexpensive, and sustainable alternative for Wolff rearrangements

Abstract: The Wolff rearrangement suffers from many drawbacks with respect to its practical execution in the laboratory. Herein, commercial LED lamps are employed as a sustainable alternative for the classic protocols typically used for Wolff rearrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 33 publications
0
29
0
3
Order By: Relevance
“…Although this photolysis phenomenon is well known for other diazocompounds using UV-light, 9 , 16 , 18 one can note here that the presence of a donor group at the aryldiazoacetates 1a and 1b (or the removal of an acceptor group, as one can observe the same trend comparing the UV-Vis absorption spectra of 2a and 2b ) is responsible for a significant bathochromic shift in their UV-Vis absorbance spectra, thus allowing the photolysis process to occur in the visible region. 10 , 16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this photolysis phenomenon is well known for other diazocompounds using UV-light, 9 , 16 , 18 one can note here that the presence of a donor group at the aryldiazoacetates 1a and 1b (or the removal of an acceptor group, as one can observe the same trend comparing the UV-Vis absorption spectra of 2a and 2b ) is responsible for a significant bathochromic shift in their UV-Vis absorbance spectra, thus allowing the photolysis process to occur in the visible region. 10 , 16 …”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the numerous protocols reported on thermal processes, photochemical studies with diazocompounds have been performed mostly several decades ago, 9 and modern applications are relatively scarce. 10 , 11 Among these, Suero and co-workers have recently demonstrated that a hypervalent iodine reagent carrying a diazoacetate moiety could be employed in a photoredox-catalyzed protocol for the C–H functionalization of a variety of arenes. 11 b In the sequence, the diazocompounds produced could be further engaged in classical reactions, thus representing an overall formal process to access carbyne equivalents.…”
Section: Introductionmentioning
confidence: 99%
“…When pyrazole 11 a is kept fixed and the aryldiazoacetate component is varied, again good yields are obtained for the corresponding insertion products 12 i – 12 s , which are produced in a range of 47–79% (Scheme , molecules 12 i – 12 s ). In addition, aryldiazoketones, such as 2‐diazo‐1,2‐diphenylethan‐1‐one 7 p or 1‐diazo‐1‐phenylpropan‐2‐one 7 q , can undergo a blue light‐promoted Wolff rearrangement (see the SI for their UV‐Vis absorption spectra), leading to the formation of ketene intermediates, which can be trapped by pyrazole to afford amides 12 t and 12 u , in 88% and 61% yields, respectively (Scheme , molecules 12 t and 12 u ).…”
Section: Resultsmentioning
confidence: 99%
“…A formação da espécie reativa ceteno no rearranjo de Wolff pode ocorrer de três maneiras 22,23 : termicamente, via catálise metálica e fotoquimicamente. O primeiro método é o menos usual dos três visto que o aquecimento a altas temperaturas (~180 °C) pode levar a formação de produtos indesejáveis diante da sensibilidade do substrato.…”
Section: Esquema 10 -Esquema Geral Para O Rearranjo De Wolffunclassified
“…Por último, mas não menos importante, o emprego de luz para a decomposição do grupo diazo é o protocolo mais eficiente dos três, essencialmente pelas condições brandas empregadas. A literatura descreve o uso de lâmpadas de mercúrio, CLC e LED como fontes de fótons nessa reação 23 .…”
Section: Esquema 10 -Esquema Geral Para O Rearranjo De Wolffunclassified